Pertumbuhan Semai Jati Putih (Gmelina arborea Roxb.) Akibat Dosis Pupuk Kandang Kambing dan Frekuensi Penyiraman - Yogi Nirwanto; Noertjahyani Noertjahyani; Yana Taryana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
An experiment was conducted to study the effect of dose goat manure and watering frequency on growth of gmelina seedling at nursarry. The experiment was carried out from April to June 2016, in Cijati village of Situraja regency Sumedang district, with the altitude 310 above sea level. The experimental design was used randomized block design (RBD) with factorial pattern consisting of two factors. The dose of goat manure consinted of five levels : with out goat manure, 50 g/polybag, 100 g/polybag, 150 g/polybag and 200 g/polybag and the watering frequency consisted of three levels : one time a day, two times a day and one time two days. The results of this experiment showed that there was interaction effect between dose of goat manure and watering frequency on stem diameter at 12 weeks after planting and shoot root ratio. Application with 150 g goat manure per polybag with watering frequency every day gave best effect on stem diameter and shoot root ratio.